2000
DOI: 10.1074/jbc.275.11.7497
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Linkage between the Type III Capsular Polysaccharide and the Bacterial Cell Wall of Group BStreptococcus

Abstract: The capsular polysaccharide of group B Streptococcus is a key virulence factor and an important target for protective immune responses. Until now, the nature of the attachment between the capsular polysaccharide and the bacterial cell has been poorly defined. We isolated insoluble cell wall fragments from lysates of type III group B Streptococcus and showed that the complexes contained both capsular polysaccharide and group B carbohydrate covalently bound to peptidoglycan. Treatment with the endo-N-acetylmuram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 37 publications
0
65
1
Order By: Relevance
“…This suggested that bfb may have a different function from the three other regulons. Since Streptococcus exopolysaccharide has beta-linked repeating disaccharides (7,43) and its capsule resembles a typical GAG, hyaluronan (34), the expression of these genes in S. gordonii may be needed for the synthesis, remodeling, and/or recycling of cell surface adhesins (glycoproteins) and/or capsule-like polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that bfb may have a different function from the three other regulons. Since Streptococcus exopolysaccharide has beta-linked repeating disaccharides (7,43) and its capsule resembles a typical GAG, hyaluronan (34), the expression of these genes in S. gordonii may be needed for the synthesis, remodeling, and/or recycling of cell surface adhesins (glycoproteins) and/or capsule-like polysaccharides.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of EPS, this association is loose and easily disrupted. In Gram-positive species, the CPS is covalently anchored to peptidoglycan by as-yet-unknown mechanisms (125).…”
Section: Fig 5 Eps and Cps Biosynthesis Pathways (A)mentioning
confidence: 99%
“…The nascent CPS is removed from the lipid through a phosphotransferase reaction and subsequently linked to a single membraneanchored repeating unit (9). The final product is a CPS that is removed from the membrane lipid and covalently attached to GlcNAc in the peptidoglycan backbone (CPS-PG) (10). This linkage effectively renders further polymerization impossible.…”
Section: Discussionmentioning
confidence: 99%
“…In S. agalactiae, the CPS is covalently attached to the cell wall peptidoglycan (10). Certain mutant strains had little CPS attached to the bacterial cell surface (Fig.…”
Section: Aberrant Cps Production and Localization In Cpsabcd Mutantmentioning
confidence: 99%
See 1 more Smart Citation